PENGARUH KEPEMIMPINAN KEPALA MADRASAH DAN KOMITE TERHADAP IMPLEMENTASI MANAJEMEN BERBASIS MADRASAH (MBM) DI MADRASAH SWASTA KOTA PAYAKUMBUH - Sahidin Sahidin (Jurnal Dedikasi Pendidikan, 2022)
The curriculum in Indonesia often changes. Changing ministers will change the name of the curriculum. This causes problems with the implementation of the learning process. And affect the quality of education. Teachers are not optimal in carrying out their duties because of misunderstanding and understanding of the new curriculum. Therefore, it is necessary to carry out guidance and training to carry out their duties and obligations. So that students understand and understand the learning taught by the teacher. And they can compete in the world of work. And no longer awkward to face the times. Thus the quality of education will also increase. Quality education will improve human resources, which are excellent and reliable in teaching and learning activities. A curriculum is a tool in education that is a program provided to teach students to change and develop students' character by education and learning objectives. The curriculum is not limited to several subjects, and schools provide and provide a comfortable learning environment for students.